2008
DOI: 10.1111/j.1438-8677.2008.00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among wild and cultivated populations of the Chinese medicinal plantCoptis chinensis(Ranunculaceae)

Abstract: To examine if the cultivation process has reduced the genetic variation of modern cultivars of the traditional Chinese medicinal plant, Coptis chinensis, the levels and distribution of genetic variation was investigated using ISSR markers. A total of 214 C. chinensis individuals from seven wild and three cultivated populations were included in the study. Seven ISSR primers were used and a total of 91 DNA fragments were scored. The levels of genetic diversity in cultivated populations were similar as those in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
(57 reference statements)
5
18
0
Order By: Relevance
“…Cultivation has not eroded the genetic diversity of the studied cultivated A. desertorum populations. Our findings are in accordance with several other cultivated plants where genetic diversity is as high as wild relatives (Hernandez-Verdugo et al 2001;Cutsem et al 2003;Khlestkina et al 2004;Shi et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Cultivation has not eroded the genetic diversity of the studied cultivated A. desertorum populations. Our findings are in accordance with several other cultivated plants where genetic diversity is as high as wild relatives (Hernandez-Verdugo et al 2001;Cutsem et al 2003;Khlestkina et al 2004;Shi et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Since the morphological characters were the result of the expression of the functional genes, however, the RAPD markers took into account not only the functional genes but also the sequences of the DNA which are not expressed. The lanes represent: M, marker (100 bp ladder plus); 1, P. indica; 2, P. arenaria; 3, P. psyllium; 4, P. lanceolata; 5, P. serraria; 6, P. coronopus; 7, P. ovata Recently, RAPDs were successfully used for studying genetic relationships in several medicinal species (Devaiah et al 2008;Rout 2006;Sarwat et al 2008;Shi et al 2008). Two sub-species of P. major were also differentiated using RAPD and ISSR markers (Wolff and Morgan-Richards 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Such a short cultivation history, in combination with the large initial population size, may be unlikely to produce a strong genetic bottleneck, resulting in significant reduction of genetic diversity and change in genetic composition of cultivated S. baicalensis . Other population genetic studies on recently-cultivated Chinese medicinal plants also suggested that high genetic diversity in cultivated populations is due to their slight cultivation bottlenecks [15-17], which provides genetic raw materials for breeding new varieties of medicinal plants.…”
Section: Discussionmentioning
confidence: 99%
“…A study of pepino ( Solanum muricatum ), a herbaceous Andean domesticate, suggested that human interchange among communities and countries in the past 50 years or so has considerably weakened the geographic differentiation of genetic diversity of cultivated pepinos [9]. For Chinese cultivated medicinal plants, such as Coptis chinensis , Magnolia officinalis , the bulking and mixing of seeds from different geographic locations are the common practice, which produced lower genetic differentiation among cultivated populations [16,17]. However, the genetic markers (ISSR and AFLP) used in those studies are biparentally transmitted, incapable of ruling out the effects of seed flow on genetic structure.…”
Section: Discussionmentioning
confidence: 99%